DEVELOPMENT OF TECHNOLOGY FOR OBTAINING HIGHLY CONCENTRATED ISOBUTYLENE - Rakhmatov Khudoyor Boboniyozovich; Khakimov Zafar Tulyaganovich; Rustamov Akmal Rustamovich; Raufzoda Shohruh Ablusaid o’g’li; Botirov Saitnabi Komil o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
The process of isobutylene hydration on sulfonic cationic catalysts is characterized by a relatively low reaction rate, the presence of a phase separation due to the mutual insolubility of water and hydrocarbons, and a high energy intensity of the process due to the need to concentrate dilute alcohol-containing solutions. However, the indisputable advantages of this method are the high degree of extraction (98–99%) of isobutylene from the hydrocarbon fraction and the high purity of the resulting monomer – 99.99 wt.% of the main substance.